Рост и развитие хомяка обыкновенного (Cricetus cricetus L.) - Самош, В.М. (Вестник зоологии, 1972)
Growth, development and longevity of Cricetus cricetus L. '. were studied under ех perimental conditions. It was established that at early stages of post-embryonic period the animals grow and develop more intensely. The longevity of Cricetus cricetus L. does not exceed 2.5 years. For their individual life Cricetus cricetus L. give only two generations. An assumption is made that every two years the natural populations of Cricetus cricetus L. are renewed which is accompanied by sharp variations in the quantity.